Schulz and Peanuts a biography - Michaelis, David (Harper, 2007)
A portrait of the late creator of the "Peanuts" comic strip evaluates how his career was shaped by his midwestern working-class origins, family losses, and wartime experiences, offering insight into how familiar storylines closely reflected Schulz's private life